Lightweight Hybrid Cryptography Algorithm for Wireless Body Area Sensor Networks Using Cipher Technique - Aizaz Raziq; Kashif Naseer Qureshi; Asfand Yar; Kayhan Zrar Ghafoor; Gwanggil Jeon (Computer assisted methods in engineering and science, 2024)
Wireless Body Area Networks (WBANs) are based on connected and dedicated sensor nodes for patient monitoring in the healthcare sector. The sensor nodes are implanted inside or outside the patient’s body for sensing the vital signs and transmitting the sensed data to the end devices for decision-making. These sensor nodes use advanced communication technologies for data communication. However, they have limited capabilities in terms of computation power, battery life, storage, and memory, and these constraints make networks more vulnerable to security breaches and routing challenges. Important and sensitive information is exchanged over an unsecured channel in the network. Several devices are involved in handling the data in WBANs, including sink nodes, coordinator, or gateway nodes. Many cryptographic schemes have been introduced to ensure security in WBANs by using traditional confidentiality and key-sharing strategies. However, these techniques are not suitable for limited resource-based sensor nodes. In this paper, we propose a Lightweight Hybrid Cryptography Algorithm (LWHCA) that uses cryptographicbased techniques for WBAN networks to improve network security, minimize network overhead and delay issues, and improve the healthcare monitoring processes. The proposed solution is evaluated in a simulation scenario and compared with state-of-the-art schemes in terms of energy consumption, and ciphertext size.